The Regulation of Insurers in Canada as an Area of Law - Fournier, Stéphane J. (Université d'Ottawa / University of Ottawa, 2025)
The regulation of insurers in Canada is a subject that has received very little academic attention, perhaps due to a combination of lack of interest and the complex and tedious challenges it poses. Nonetheless, it is a vitally important area. Governments in Canada regulate insurers, including their insurance products, given their very important roles and the position of power that insurers have vis-à-vis their customers. As a result, this regulation seeks two key objectives: to protect the financial rights and interests of insurance customers and certain other stakeholders, and to contribute to public confidence in the insurance sector and the financial system as a whole. Governments use the following two key means to pursue these objectives: a) prudential regulation, which incites insurers to prudently identify, control and manage the various risks they face, and thereby provides some assurances that insurers will be able to live up to their financial obligations; and, b) market conduct regulation, which, in regards to insurance products, incites insurers to treat their customers fairly throughout the lifecycle of these products. This paper will first explore the fundamentals necessary to examine these two types of regulation, including how they compare to insurance law. The paper will then examine the aims of, and rationale for, these types of regulation, and then expose the related regulators. Lastly, it will reveal the means by which these regulators regulate and supervise insurers within their perimeter.